The Amara Raja Group (A) : building HRM capabilities - Varkkey, Biju; Shaik, Farheen Fathima (London : Indian Institute of Management, Ahmedabad, 2019)
The announcement of the 10-year vision "Vision 2025" for Amara Raja Group (ARG) by its Chairman, Ramachandra Naidu Galla, in December 2015 sets in motion a massive organisational scale-up. Galla makes public ARG's target to employ 60,000 employees and achieve a turnover of INR 600 billion by the end of 2025. ARG sets an interim goal of INR 180 billion in revenue by 2020. In January 2018, a little over two years after the unveiling of Vision 2025, Jaikrishna, ARG's Group Human Resources (HR) Head, is pondering whether the existing HR structure is prepared to cater to the organisation's future needs and how it can become an enabler for ARG's growth.
Originally Published InVarkkey, B., & Shaik, F. (2019). Amara Raja Group (A): Building HRM Capabilities. IIMA/HRM0241. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Human capital -- Case studies; Corporations -- Growth -- Case studies